2002
DOI: 10.1002/1521-4141(200201)32:1<122::aid-immu122>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Specific peptide-mediated immunity against established melanoma tumors with dendritic cells requires IL-2 and fetal calf serum-free cell culture

Abstract: Melanoma, despite its aggressive growth characteristics, is an antigenic tumor expressing several characterized neo‐ and differentiation antigens. Dendritic cells (DC) when pulsed with definedpeptides have been shown to effectively induce melanoma‐specific T cell responses in humans and mice. These protect animals from challenge with melanoma, but so far have failed to induce significant tumor regressions. To study the efficacy of DC‐based anti‐tumor vaccinations, we set up a therapeutic model using C57BL/6J m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…In contrast, some studies have demonstrated that immunization with syngenic DC alone (in the absence of tumor Ag) can induce NK cell-dependent antitumor responses against melanoma, colon, or lung carcinoma (17,20,23). We have previously noted that immunization with syngenic DC in the absence of tumor Ag can induce antimelanoma immunity in the prophylactic setting, but only if FCS Ags are present in both the DC and the melanoma culture medium (37,39). Unless rigorous attempts are made to exclude FCS from all steps of either DC (37) or melanoma (39) culture, anti-FCS responses could be mistaken for the action of the innate immune response, including NK cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some studies have demonstrated that immunization with syngenic DC alone (in the absence of tumor Ag) can induce NK cell-dependent antitumor responses against melanoma, colon, or lung carcinoma (17,20,23). We have previously noted that immunization with syngenic DC in the absence of tumor Ag can induce antimelanoma immunity in the prophylactic setting, but only if FCS Ags are present in both the DC and the melanoma culture medium (37,39). Unless rigorous attempts are made to exclude FCS from all steps of either DC (37) or melanoma (39) culture, anti-FCS responses could be mistaken for the action of the innate immune response, including NK cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…For the in vitro cytokine release assays, splenocytes were cultured at 2 3 10 6 /ml in the presence or absence of S. salivarius K12 in 96-well round-bottom plates (Nunc, Auckland, New Zealand) for 18 h. Soluble IFN-g was measured by ELISA (BD Biosciences). In vitro cytotoxicity of lymph node or splenic NK cells against the B16-OVA melanoma line was tested by plating 250 target B16-OVA cells in 10 ml R10 in triplicate in Terasaki wells (37). Effector NK cells, isolated from lymph node or spleen using the untouched NK cell Isolation Kit II (Miltenyi Biotec, Pharmaco, Auckland, New Zealand), were overlaid in 5 ml R10 at a 100:1 E:T ratio.…”
Section: Preparation and Stimulation Of DCmentioning
confidence: 96%
“…The limited efficacy of cultured DC pulsed with the TRP2 aa180-188 peptide epitope may be enhanced by coadministration of immunostimulatory cytokines such as IL-2 12,36 or by multiple injections of peptide-pulsed DC. 11 As an alternative strategy, Wang et al 13 attached the TRP2 aa180-188 peptide to the protein transduction domain of HIV TAT, which leads to prolonged antigen presentation by DC.…”
Section: Discussionmentioning
confidence: 99%
“…3B). Despite the well documented nonspecific protective effect conferred by vaccination with BM-DC alone (17)(18)(19)(20), targeting the response to SPAS-1 (SNC9-H 8 ) led to a significantly greater delay in tumor growth rate compared with vaccination with SL8-pulsed BM-DC (P Ͻ 0.05) (Fig. 3A), confirming that SNC9-H 8 was indeed a target of the anti-TRAMP tumor T cell response in vivo.…”
Section: Identification Of the Spas-1 T Cell Epitopementioning
confidence: 99%